G112 Chorioamnionitis in preterm infants is not associated with brain size and maturation at term equivalent age. (27th April 2015) - Granger, CL; Spittle, A; Doyle, LW; Pyman, J; Walsh, JM; Cheong, JLY
Abstract : Introduction: Chorioamnionitis is a risk factor for adverse neurodevelopment in preterm infants but the effect on brain size or maturation is unclear. This study aimed to determine the association between perinatal characteristics and histological chorioamnionitis in a cohort of preterm infants. We also aimed to establish the association between chorioamnionitis and brain size and maturation. Methods: A large prospective cohort of preterm infants was identified and data from placental histology reports were collected and chorioamnionitis, characterised into either no inflammatory response, maternal response only or both fetal and maternal response. All infants had brain MRI scans at term equivalent age. T1 and T2 weighted images were systematically scored for size of cerebral structures, degree of myelination, gyral maturation, signal abnormalities and presence of cysts. Differences between groups were compared using linear regression for continuous variables and logistic regression for categorical variables. Results: Of the 237 infants included in this study, 58 (24.5%) had histological evidence of chorioamnionitis. Table 1 summarises the demographic data. Infants with evidence of chorioamnionitis on placental histology had higher rates of preterm delivery (p < 0.0001), low birth weight (p = 0.04) and prolonged rupture of membranes (p < 0.0001). Those with chorioamnionitis had higher rates of intraventricular haemorrhage (p < 0.0001). Chorioamnionitis, however, was not associated with brain injury or delayed maturation on qualitative MRI assessment. The MRI scoring data is shown in Table 2 .